Biodegradation of Gramineous Lignocellulose by Locusta migratoria manilensis (Orthoptera: Acridoidea) - Zhang, Hongsen; Li, Zhenya; Zhang, Hongfei; Li, Yan; Wang, Fengqin; Xie, Hui; Su, Lijuan; Song, Andong (Frontiers in Bioengineering and Biotechnology, 2022)
Exploring an efficient and green pretreatment method is an important prerequisite for the development of biorefinery. It is well known that locusts can degrade gramineous lignocellulose efficiently. Locusts can be used as a potential resource for studying plant cell wall degradation, but there are few relative studies about locusts so far. Herein, some new discoveries were revealed about elucidating the process of biodegradation of gramineous lignocellulose in Locusta migratoria manilensis. The enzyme activity related to lignocellulose degradation and the content of cellulose, hemicellulose, and lignin in the different gut segments of locusts fed corn leaves were measured in this study. A series of characterization analyses were conducted on corn leaves and locust feces, which included field emission scanning electron microscopy (FE-SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction pattern (XRD), and thermogravimetric (TG) analysis. These results showed that the highest activities of carboxymethyl cellulase (CMCase), filter paper cellulase (FPA), and xylanase were obtained in the foregut of locusts, which strongly indicated that the foregut was the main lignocellulose degradation segment in locusts; furthermore, the majority of nutritional components were absorbed in the midgut of locusts. The activity of CMCase was significantly higher than that of xylanase, and manganese peroxidase (MnPase) activity was lowest, which might be due to the basic nutrition of locusts being cellulose and hemicellulose and not lignin based on the results of FE-SEM, FTIR, XRD, and TG analysis. Overall, these results provided a valuable insight into lignocellulosic degradation mechanisms for understanding gramineous plant cell wall deconstruction and recalcitrance in locusts, which could be useful in the development of new enzymatic pretreatment processes mimicking the locust digestive system for the biochemical conversion of lignocellulosic biomass to fuels and chemicals.